Implementation of Yasinan Organizational Culture in Forming the Islamic Character of Students - Putri Rahayu; Makmur Syukri (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
The rapid flow of modernization brings great challenges to the world of education, especially in terms of moral decline and character crises among students. Spiritual and social values ??are starting to be displaced by environmental influences less supportive of moral formation. Therefore, this study aims to analyze the implementation of the Yasinan organizational culture in forming the Islamic character of students at MTs Al-Ittihadiyah Mamiyai Medan. The research method used is descriptive qualitative with a phenomenological approach. There were two informants in this study: the principal and teachers at MTs Al-Ittihadiyah Mamiyai Medan. Data collection techniques used observation, interviews, and documentation. Data analysis techniques through the stages of Miles and Huberman: data reduction, data presentation, and drawing conclusions and verification.  The study results indicate that the Islamic organizational culture in the form of Yasinan activities at MTs Al Ittihadiyah Mamiyai Medan has succeeded in forming the religious character of students through structured and sustainable spiritual habits. This activity is not only a routine of worship but also plays a role as a value system that instills discipline and responsibility and strengthens awareness of the importance of worship as part of everyday life. This culture reflects the application of Islamic values ??in educational organizations, which align with the teachings of the Qur'an and Hadith. It can create positive behavioral norms rooted in the shared beliefs of all members of the madrasah